TEROBOSAN KREATIF KEPOLISIAN PERAIRAN POLDA BANTEN DALAM PELAKSANAAN PEMELIHARAAN KEAMANAN MASYARAKAT DAN PENEGAKAN HUKUM DI PERAIRAN SELAT SUNDA - Danial, Danial (Lampung University, 2015)
Marine Police Regional Police Banten Province is breakthrough in the development of creative, aware of the importance of knowledge of the social and cultural life of the operational environment. However, the problem is: First, how the pattern of development of the concept of Creative Breakthroughs Marine Police Banten ?; Second, how the implementation of the concept of creative breakthrough Marine Police Banten?. The results showed that the First, Pattern Creative Breakthrough Development undertaken in the framework of Banten Water Police Pushing Water existence in Banten Police are doing synchronization and coordination with the Department of Maritime Province of Banten in terms of the measurement vessel, Formulation of Local Regulations related to service to the fishermen and the plan of Units waters; Secondly, optimization of local government support, Academics to Overcome situation, needs and implementing creative breakthroughs Marine Police Banten in order to protect, Protects, Serving Society, and Law Enforcement The Regional Water can be embodied through preemptive action, preventive and educative as well as ongoing collaboration with the form as a container maritime forum gathering agencies in charge of maritime waters and ports in Province of Banten.Keywords: Creative Breakthroughs, Marine Police, Security, Law Enforcement, Sunda Strait